PENGEMBANGAN POTENSI LOKAL MELALUI PEMBERDAYAAN LINGKUNGAN DAN UMKM PADA MASYARAKAT PESISIR - Muhammad Nizar; Mukhid Mashuri (LPPM Universitas Yudharta Pasuruan, 2018)
Changes in the behavior of housewives before training and some mentoring are the emergence of awareness of housewives, who are members of the PKK organization, in increasing family profits, before training and mentoring, mothers still do not understand in making shrimp nuggets, where most of the results, shrimp are only sold conventionally, at low prices. But after the implementation of training and mentoring, can produce nuggets that are better and better, because they already understand about good nuggets making techniques. In addition, it increases awareness of the importance of the role of housewives in helping family income income which is no longer the responsibility of the husband alone. Training and counseling in the manufacture of shrimp nuggets in the future can be followed up to continue mentoring, so that from home products can be an extraordinary home industry. Home industry can be in the sense that it can be managed individually or as a group of mothers from Tambak Lekok residents. If home industry, especially individually and carried out mentoring continues, it is possible to submit the legalization of the Certificate of Household Industry Food Products (SPP-IRT), namely by utilizing the results of Technology owned by the University of Yudharta Pasuruan in the context of downstreaming.